Spoštljivost v deliberaciji - Petrič, Gregor (Teorija in praksa, 2015)
Respect in communication is one of the key criteria for good deliberation, yet it is one of the unclearest concepts in the field of deliberation research with many critical issues in approaches to its measurement. The main purpose of the article is to present theoretical challenges in an attempt to produce a clearer definition of respect in deliberation, which then serves as a criterion to evaluate the validity of existing approaches to measuring respect in deliberation. On the basis of understanding respect as a factor influencing other components of deliberation, a hypothesis is formed which serves to analyse the criterion%s validity. When applying a logistic regression on a sample of discussions on the Family Act, the weak criterion validity of the alternative measurement instrument was found. However, this warrants further optimisation of the measurement instrument.
Keywords: communication; Deliberative democracy; Družinski zakonik; Družinsko pravo; Family law; komuniciranje; Posvetovalna demokracija; Respect; spoštljivost; Spoštovanje